Development of decellularized-matrix based breast cancer 3D in vitro tumor models for therapeutic screening - Ferreira, Luís Pedro Correia Pinto (2024)
Impacting all stages of tumor progression and therapeutic efficacy, the breast cancer ECM is evermore recognized as a crucial component in breast cancer progression. However, despite the urgency in expediting the discovery and translation of novel effective breast cancer treatments, most preclinical in vitro models fail to recapitulate the complex interplay occurring in the three-dimensional tumor microenvironment (TME), especially in the context of cell and extracellular matrix (ECM) interactions. Despite the increasing adoption of 3D in vitro tumor models such as spheroids, these scaffold-free platforms still generally lack any prior representation of native ECM components of the TME. Alternatively, decellularized extracellular matrix (dECM)-based models are arising as valuable alternatives to bioengineer more physiomimetic tissue-specific and tumor-specific platforms within which cells can self-arrange and interact with ECM components, in a more biomimetic mode. Therefore, the main goal of this thesis was to drive forward the development of advanced 3D in vitro models of breast cancer, capable of more faithfully recapitulating the interactions established between breast cancer’s key ECM components and its heterotypic cellular landscape. A comprehensive overview of the changes in breast cancer TME landscape and on the importance of dECM-based biomaterials for in vitro tumor modeling is provided for contextualization of the current state-of-the art of the field. The bioengineering of breast cancer-stroma heterotypic spheroids is focused with the aim to demonstrate these model’s ability to serve as a platform to test living therapeutics. The screening of chemo-photothermal nanotherapeutic loaded mesenchymal stem cell (MSC) in 3D tumor models enabled to validate their tumoritropic delivery and access their preclinical performance. Seeking to advance breast cancer spheroid models, tissue-specific mammary dECM fibrillar fragments was then integrated within the process of spheroid formation, leading to new pathways for high-throughput compatible fabrication of ECM-enriched tumor spheroids. Lastly, an innovative methodology gathering on a fully exogenous enzyme free photoacoustic processing of breast-tissue specific dECM enabled the formulation of dECM inks and their processing into 3D living constructs by employing superhydrophobic surfaces and automated biofabrication technologies. Holistically, the newly developed methodologies provide means to generate high-throughput compatible 3D tumor models that more closely portray both stroma and ECM interactions with cancer cells. As such, given this approximation to more physiomimetic and predictive models, these are thus expected to accelerate the discovery of more effective therapeutic combinations by providing new grounds in which to preclinically analyze future therapies.